Problematika Presidential Threshold Dalam Ketatanegaraan Indonesia Perspektif Fiqih Siyasah - Mutaqin Mutaqin; Ema Nurkhaerani; Ubaidillah Ubaidillah (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2024)
The implementation of Presidential Threshold provisions based on article 222 of Law Number 7 of 2017 concerning General Elections is an effort to create an effective and stable government. In its application, this threshold provision presents pros and cons because it also gives rise to many other, much bigger problems. This research aims to find out how the Presidential Threshold provisions are based on Law Number 7 of 2017 concerning General Elections and how these provisions are in Indonesia from the perspective of siayash fiqh maslahah murlah theory. The method used in this research is qualitative and uses an empirical-normative approach. Data collection techniques are literature/library research, interviews and study of statutory regulations. The results of this research found that the Presidential Threshold provision is the minimum limit for a political party to obtain votes in the previous legislative election to nominate a candidate pair for president and vice president. From the maslahah murlah perspective, this Presidential Threshold provision has a lot of potential for harm.